2009 Asia Pacific Microwave Conference 2009
DOI: 10.1109/apmc.2009.5384469
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and design of compact two-way Wilkinson power dividers using coupled lines

Abstract: transformers are used in both designs, which provide even mode impedances of 70.7 X with a line spacing of 0.56 mm [8]. The area of the folded layout is 30% less than the unfolded layout. The simulated and the measured results are compared in Figures 8-10.In Figure 8, the insertion loss for both designs is shown. Because the layouts are symmetrical, only |S 21 | is compared with the simulation. It is found that the measured data fits the simulations well. The insertion loss at the center frequency is 3.2 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 2 publications
0
45
0
Order By: Relevance
“…Mathematical calculation and selected examples are proved that: by suitable adjusting even-and odd-mode characteristic impedances and their electrical lengths, perfect matching of proposed WPD can be realized without any extra compensation structure. Although bandwidths of proposed WPD become a little narrow as coupling strengths increased, compared with previous work in [7], the bandwidths didn't decrease rapidly in the realizable design range of 1 < < 3.…”
Section: Design Procedures and Examplesmentioning
confidence: 83%
See 1 more Smart Citation
“…Mathematical calculation and selected examples are proved that: by suitable adjusting even-and odd-mode characteristic impedances and their electrical lengths, perfect matching of proposed WPD can be realized without any extra compensation structure. Although bandwidths of proposed WPD become a little narrow as coupling strengths increased, compared with previous work in [7], the bandwidths didn't decrease rapidly in the realizable design range of 1 < < 3.…”
Section: Design Procedures and Examplesmentioning
confidence: 83%
“…Until now, S-Type section without any extra compensation structure has not been discussed in microstrip line structure. Theoretically, coupled line section WPDs [7,8] could be only designed in stripline structure, where the electrical lengths between even-and odd-mode are defined equally. Under the condition of microstrip line structure, extra lumped elements and extra coupled line section are compensated the characteristic impedance and phase difference [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many efforts have been made to develop high-performance power dividers [2][3][4][5][6][7]. After decreasing the inherent circuit size of the conventional Wilkinson power divider, a coupled-line section is used to design compact power divider in [8]. From the analyzed results of [8], it can be found that the odd-mode impedance of the coupled line is a free design variable.…”
Section: Introductionmentioning
confidence: 99%
“…After decreasing the inherent circuit size of the conventional Wilkinson power divider, a coupled-line section is used to design compact power divider in [8]. From the analyzed results of [8], it can be found that the odd-mode impedance of the coupled line is a free design variable. Therefore, the design tradeoffs among the output-ports matching, isolation and the odd-mode impedance can be easily achieved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation